PENATALAKSANAAN BAYI BARU LAHIR NY. P DENGAN ASFIKSIA SEDANG DI RUMAH SAKIT UMUM DAERAH BREBES TAHUN 2024 - Ahmad Ridlo; Himatul Khoeroh (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Neonatal asphyxia is a condition when a newborn baby lacks oxygen shortly after birth. This condition can be fatal because it has the potential to cause difficulty breathing in babies which can have an impact on infant death. Asphyxia is one of the highest problems at Brebes Regional Hospital in 2023. This study aims to describe the management of asphyxia cases through a study of subjective and objective data, analysis and management. This study is a qualitative descriptive type with a case study approach. Initial informants with acidental sampling techniques. Data collection methods through in-depth interviews, observation and documentation of 1 main informant, namely Mrs. P, and additional informants in the family of Mrs. P, the midwife on duty, a pediatrician and an obstetrician. Data validity is carried out on one of the triangulation informants as a key, namely the VK room coordinator midwife. The results of the study on subjective data, Mrs. P's baby was born perabdominally, did not cry immediately, and had weak muscle tone. Objective data obtained APGAR Score 4,5,6 results of anthropometric examination, namely weight 3440 grams, Length 51 cm, head circumference 33 cm, chest circumference 32 cm, and there is a chest crack when breathing, with a respiratory rate of 65x / minute, heart rate > 100 which is 140x / minute and the general condition of the baby is weak and no reflexes were found. Data analysis with Moderate Asphyxia. Management of newborns with asphyxia at Brebes Hospital includes oxygenation and resuscitation and asphyxia is resolved.